A new species of Trixis (Nassauvieae, Asteraceae) from the Center of Plant Diversity of Cabo Frio, Brazil - Monge, Marcelo; Saavedra, Mariana Machado (Phytotaxa, 2020)
Trixis salina is a new endemic species from restinga vegetation of the Center of Plant Diversity of Cabo Frio region in Rio de Janeiro state, southeastern Brazil. It grows in rocky ravines, rocky shores, and in shrubby restinga. The new species is morphologically similar to Trixis antimenorhoea; however, they differ in habit, branches, trichomes, leaf morphology, involucral bracts, and number of flowers per head. The preliminary conservation status assessment shows that Trixis salina must be included in Endangered (EN) category.